The structure of the Western and Central parts of the Ukrainian schield. Controversial issues - О. B. Gintov; M. I. Orlyuk; V. A. Entin; I.K. Pashkevich; S. V. Mychak; M. I. Bakarzhieva; L. M. Shimkiv; A. V. Marchenko (Геофизический журнал, 2018)
Some controversial issues of composing the Scheme of the fault megablock tectonics of the western half of the Ukrainian shield in connection with the decision of the Interdepartmental Tectonic Committee of Ukraine on drawing up the Tectonic map of the Ukrainian shield at a scale of 1:500 000 have been considered. Geophysical data must be more fully taken into account and used in detail and objectively reflecting both the surface and the deep structure of the Earth’s crust of the shield while drawing up such a Scheme. The latest maps of anomalous magnetic and gravitational fields, a map of the topography of the Moho surface and other materials are given, the analysis of which gives grounds for a number of conclusions on specific structures of the western and central parts of the region. It has been established that the formation of a typical megablock structure of the Ukrainian shield began not earlier than in the Neoarchean. It is difficult unambiguously to establish and trace the investigated Archean fault zones in the part of the shield  at the present time, and sometimes practically it is almost impossible, since the Early Proterozoic processes of regional granitization and dynamometamorphism radically changed the composition and structure of the earth’s crust. Geophysical data, supported by geological and tectonophysical observations, clearly record the Proterozoic fault zones, which began to form after 2.5 billion years ago. They cross and deform both the Archean and the Early Proterozoic granitoid complexes, accompanied by intensive diffusion, metasomatism and ore formation. It is proved that the Archean-Early Proterozoic structural-formation complexes (SFC), mapped within the shield, cannot and should not be artificially linked with the Proterozoic fault-megablock structure, which was formed at the end of the Early Proterozoic and superimposed on the SFC. It seems like the dubious and outdated thesis about the subhorizontal-floor structure of the Early Precambrian crust of the Ukrainian shield, according to which the structural floors of the crust are formed one above another by stratometamorphic complexes characterized by a directly proportional relationship of age and the degree of regional metamorphism of the rocks. This concept does not take into account the significant role of horizontal motions of lithospheric blocks, which cause the redistribution and localization of PT conditions in the earth’s crust.